2021
DOI: 10.3390/jpm11121368
|View full text |Cite
|
Sign up to set email alerts
|

What Influences Women to Adhere to Pelvic Floor Exercises after Physiotherapy Treatment? A Qualitative Study for Individualized Pelvic Health Care

Abstract: Conservative treatment of pelvic floor dysfunction (PFD) includes therapeutic exercise for pelvic floor muscle (PFM) training or other complementary exercise modalities, such as hypopressive exercises. However, the long-term effectiveness of the conservative treatment depends on a patient’s adherence to the exercises and the integration of professional health advice into their daily life. The objective of this study was to establish the adherence experience of women with diagnosed PFD in home-based exercises a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 33 publications
0
9
0
3
Order By: Relevance
“…Studies that conducted a follow-up after the intervention reported women’s perseverance in terms of the newly-acquired voiding habits [ 16 ] and PFM exercises [ 15 , 16 ], even though the follow-up was not supervised by professionals. Periodic face-to-face follow-up meetings may contribute to promoting adherence to the exercise programme or healthy behaviours, correcting misconceptions, answering questions, or modifying exercises based on individual progression [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies that conducted a follow-up after the intervention reported women’s perseverance in terms of the newly-acquired voiding habits [ 16 ] and PFM exercises [ 15 , 16 ], even though the follow-up was not supervised by professionals. Periodic face-to-face follow-up meetings may contribute to promoting adherence to the exercise programme or healthy behaviours, correcting misconceptions, answering questions, or modifying exercises based on individual progression [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we discovered that social support from a variety of sources, including information and advice provided by the healthcare team, support from family members, peer support, and support from group organisations such as the local community, were all positive facilitators of pelvic oor rehabilitation behaviours in pregnant patients. Navarro et al reported that the feedback provided by health professionals was also a condition for adherence to exercise [42].…”
Section: Discussionmentioning
confidence: 99%
“…Adherence rates to PFMT are higher with supervised PFMT, yet wane over time with self‐directed PFMT, with rates as low as 32% at 12 months 29 . In a study of 31 women, adherence to home PFMT was dependent on the efficacy and simplicity of the exercise program, personal experiences with PFMT, as well as intrinsic factors (self‐awareness or beliefs), and extrinsic factors (professional feedback) 30 . The largest barriers to adherence are time and remembering to exercise.…”
Section: Oab Therapy Adherencementioning
confidence: 99%
“…29 In a study of 31 women, adherence to home PFMT was dependent on the efficacy and simplicity of the exercise program, personal experiences with PFMT, as well as intrinsic factors (selfawareness or beliefs), and extrinsic factors (professional feedback). 30 The largest barriers to adherence are time and remembering to exercise. Therefore, simplified, effective, mutually agreed upon programs with suggestions for incorporating them into daily routines may increase adherence.…”
Section: Behavioral Therapy Adherencementioning
confidence: 99%